2015
DOI: 10.1080/10408347.2015.1064759
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Applications of Transport Through Bulk Liquid Membranes

Abstract: This review discusses the results of research in the use of bulk liquid membranes in separation processes and preconcentration for analytical purposes. It includes some theoretical aspects, definitions, types of liquid membranes, and transport mechanism, as well as advantages of using liquid membranes in laboratory studies. These concepts are necessary to understand fundamental principles of liquid membrane transport. Due to the multiple advantages of liquid membranes several studies present analytical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…Assessing in time of the reduced concentrations of indole-3-acetic acid demonstrated that its pertraction through bulk liquid membrane transport system is realized after a kinetic model of consecutive irreversible first order reactions according to the equation 1: (1) where k 1 and k 2 represent pseudo-first-order apparent membrane entrance and exit rate constants, s -1 ; According to this model kinetic the variation in time of reduced concentrations respects relationships: Through the fitting of equations 8-10 with the experimental data pseudo-first-order apparent membrane entrance and exit rate constants k 1 and k 2 are obtained. From the dependence Rm = f (t) one can determine the maximum concentration of indole-3-acetic acid from the membrane.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessing in time of the reduced concentrations of indole-3-acetic acid demonstrated that its pertraction through bulk liquid membrane transport system is realized after a kinetic model of consecutive irreversible first order reactions according to the equation 1: (1) where k 1 and k 2 represent pseudo-first-order apparent membrane entrance and exit rate constants, s -1 ; According to this model kinetic the variation in time of reduced concentrations respects relationships: Through the fitting of equations 8-10 with the experimental data pseudo-first-order apparent membrane entrance and exit rate constants k 1 and k 2 are obtained. From the dependence Rm = f (t) one can determine the maximum concentration of indole-3-acetic acid from the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the bulk liquid membranes has been applied in many fields of research, due to their ability to transport certain compounds of interest, such as: analytical chemistry, organic chemistry and inorganic chemistry; biomedical engineering, pharmaceutical industr y, chemical industr y, biotechnology, environmental protection, as well as in wastewater treatment. Separation, removal or recovery of organic compounds, toxic metals and products of fermentation were realized using the system of de transport through liquid membranes [1][2][3][4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes and porous materials are key elements in many industrial fields [1][2][3][4][5][6], whether in catalysis [7], sensor design [8][9][10][11] or in gas [12] and liquid phase separation processes [13][14][15][16]. In the later field, membranes are especially studied in ion extraction using pertraction.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent studies suggest that competitive ligand–stripping voltammetry methods overestimate metal complexation by DOM (Dissolved organic Matter) and therefore underestimate metal concentration in comparison with model predictions (WHAM VII) [ 16 ]. Among others separation methods, solid phase and liquid-liquid extractions have been extensively used, while recently, liquid membranes have been described as a clean, useful and powerful alternative to these classical methods [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%